MO212: Updated Interim Results of A Phase 1/2 Study to Investigate the Safety, Tolerability, Pharmacokinetics, Pharmacodynamics and Clinical Activity of BION-1301 in Patients With IGA Nephropathy. (3rd May 2022) - Barratt, Jonathan; Kooienga, Laura; Hour, Billy; Agha, Irfan; Schwartz, Brian; Sorensen, Bess; Lo, Jeannette; King, Andrew; Sathaliya, Taher; Prasad N Iyer, Sai; Endsley, Aaron; Glicklich, Alan
Abstract: BACKGROUND AND AIMS: Immunoglobulin A nephropathy (IgAN) is the leading cause of primary glomerulonephritis worldwide with limited treatment options, especially for high-risk patients [1]. BION-1301 is a novel humanized monoclonal antibody that blocks a proliferation-inducing ligand (APRIL), a soluble factor that has been shown to be elevated in patients with IgAN and is correlated with poorer outcomes, including increased proteinuria and decreased eGFR [2, 3]. APRIL promotes IgA class switching, the survival of IgA-secreting plasma cells and the excess production of a galactose-deficient variant form of IgA1 (Gd-IgA1), which is an initiating step in IgAN pathogenesis. This leads to the generation of anti-Gd-IgA1 autoantibodies, considered to be the first 'hit' in the multi-hit pathogenesis of IgAN, and the formation of nephritogenic immune complexes that deposit in the kidney, resulting in inflammation and damage [2–4]. Blocking APRIL with BION-1301 is a novel approach to address the underlying pathogenesis of IgAN by reducing circulating levels of Gd-IgA1 and preventing the formation of pathogenic immune complexes. In a Phase 1/2 study of BION-1301 in healthy volunteers (HV), BION-1301 was well-tolerated with no serious adverse events (SAEs), demonstrated a pharmacokinetic (PK) half-life > 30 days and durable dose-dependent reductions in free APRIL (fAPRIL), Gd-IgA1, IgA and IgM, with a lesser effect on IgG [5]. Here we present updated interim results from Part 3 of the study that characterize the safety, PK/PD profile and preliminary efficacy of BION-1301 initially administered intravenously (IV), then subcutaneously (SC), in patients with IgAN. METHOD: Parts 1 and 2 of the Phase 1/2 study (NCT03945318) assessing single and multiple ascending doses of BION-1301 in HV are complete. Part 3 is an ongoing, open-label, multicohort design in patients with IgAN treated with BION-1301 for up to 1 year. Key eligibility criteria for Part 3 include: (i) biopsy-verified diagnosis of IgAN within the past 10 years, (ii) baseline urine protein excretion ≥ 0.5 g/24 h or UPCR ≥ 0.5 g/g and (iii) stable/optimized dose of ACE-I/ARB (or intolerant). Cohort 1 receives 450 mg of BION-1301 administered IV every 2 weeks. After at least 24 weeks of IV dosing, patients' transition to 600 mg of BION-1301 administered SC every 2 weeks. Cohort 2 receives 600 mg of BION-1301 SC every 2 weeks. To evaluate PK/PD effects of BION-1301, serum levels of BION-1301, fAPRIL, anti-drug antibodies (ADA), neutralizing antibodies (NAbs) and Gd-IgA1 were quantitated using ELISA-based immunoassays. RESULTS: Updated data from Cohort 1 will be reported. BION-1301 was well-tolerated in patients with IgAN receiving a 450 mg IV dose every 2 weeks for at least 24 weeks, with no SAEs or early terminations due to AEs. Durable reductions in serum levels of fAPRIL and immunoglobulins were observed in patients with IgAN. Clinically meaningful reductions in proteinuria were seen as early as 12 weeks and were associated with the reduction in Gd-IgA1 levels. CONCLUSION: BION-1301 offers disease-modifying potential by directly targeting the initiating mechanisms underlying the multi-hit immune pathogenesis of IgAN, which is not addressed with currently available treatments. Promising early mechanistic biomarker and clinical activity responses support the therapeutic potential of BION-1301 in IgAN.